Early Childhood Teachers’ Perceptions at "Rumah Bermain Ku" Regarding Digital Books and Printed Books as Learning Media - Zakiah Zakiah; Tiara Sekar Harnum; Amelia Vinayastri (Indonesian Journal of Early Childhood Educational Research (IJECER), 2025)
This stydy aims to explore teachers' perceptions regarding the use of digital books and printed books in early childhood education. Using a qualitative phenomenological approach, this study involved six teachers from one private early childhood education institution selected purposively, namely PAUD Rumah Bermain Ku in Depok City. Data were collected through observation, documentation, and in-depth interviews. The analysis included stages of reduction, display, and conclusion. The results showed that teachers preferred printed books, which were considered more appropriate for early childhood development, effective in maintaining children's focus, and supporting interactions between teachers and students. However, challenges for digital books included distractions, infrastructure issues, and a lack of teacher training. To increase digital book usage, actions like digital literacy training and providing more devices are needed. Teachers should combine printed and digital resources and collaborate on effective learning strategies.